DELVING INTO PRESCHOOL TEACHERS’ APPROACHES AND KNOWLEDGE ON SOCIAL SKILLS AND ITS RELATIONSHIP TO SCHOOL READINESS - Rafiah Kassim; Dr Fatin Aliana Mohd Radzi; Dr. Sharifah Muzlia Syed Mustafa (Journal of Islamic, Social, Economics and Development, 2023)
The adage ‘it does not take too much schooling to become a preschool teacher’ needs addressing. Teachers play a pivotal role in educating preschoolers’ educational journey, by preparing children for overall readiness to school and to learn. The first objective of this qualitative study is to discover if the preschool teachers’ teaching approaches on social skills. Secondly, it is to determine teachers’ knowledge and understanding on the relationship between social skills and school readiness towards preschoolers’ readiness for future success. The data retrieved were from two Malaysian preschools with ten teachers as respondents and interview questions were recorded according to protocols. The interviewing and observation session took over a period of three days for two weeks for each school. The study’s conceptual 2 framework discusses on the two facets of social skills namely communication and emotion, with theories and approaches to nurture school readiness. The finding through interviews and questionnaire found that teachers from School A and B understood and has knowledge of social skills. However, during numerous visits to both school researcher’s findings indicated there is a difference in teaching approaches between School A and B. In School A, researcher saw the application of the Montessori approach, whilst in School B researcher found there was no specific approach. Henceforth, the study observed the relapse between social skills and school readiness due to lack of teaching approaches. Thus, reintroducing and reshaping social skills curriculum with theories and approaches that relates to school readiness. These contributions allow preschoolers to enjoy the benefit of learning with knowledgeable teachers’ curriculum and teaching methods that has been up-scaled to meet the needs of today’s children.